Answer:
f(x) = -1.25
Step-by-step explanation:
Substitute x with -5, so our equation would look this:
Note: We were already given the value of x
f(x) = 1/4(-5)
Multiply 1/4 and -5:
1/4 * -5 = -1.25
So, our answer would be -1.25
-1.25
Step-by-step explanation:In order to find the answer to your question, we're going to need to plug in a number to the variable x.
We know that x = -5
This means that whenever you see x, you would replace it with what it equals to. In this case, we would plug in -5 to x, since that's what it equals to.
Your equation would look like this:
[tex]\frac{1}{4}( -5)[/tex]
Now, you would solve to get your answer.
[tex]\frac{1}{4} (-5)=-1.25\\\\\text{1/4 is the same as 0.25} \\\\0.25(-5)=-1.25[/tex]
Once you're done solving, you should get -1.25
This means that f(x) = -1.25
I hope this helps you out.Good luck on your academics.Have a fantastic day!Diem is using a cylinder shape container to hold 42 in³ of liquid. The height of the container is 3 inches tall.
What is the best approximation for the radius of the container?
1.1 in.
2.1 in.
3.5 in.
4.5 in.
Answer:
The correct answer option is B. 2.1 inches.
Step-by-step explanation:
We are given that the cylinder is to hold 42 in³ of liquid while the height of this container is 3 inches tall.
We are to find the best approximation for the radius of this container.
We know that the formula for the volume of a cylinder is given by:
Volume of cylinder = [tex]\pi r^2h[/tex]
Substituting the given values in the above formula to get:
[tex]42=\pi \times r^2 \times 3[/tex]
[tex]r^2 = \frac{42}{\pi \times 3 }[/tex]
[tex]\sqrt{r^2} = \sqrt{4.46}[/tex]
r = 2.1 inches
Complete the three-by-three magic square (that is,the sums of the numbers in each row, in each column and in each of the diagonals are the same) using
[tex]\displaystyle\\\text{We will use numbers from 1 to 9.}\\\\1+2+3+4+5+6+7+8+9=\frac{9(9+1)}{2}=\frac{9\times10}{2}=\frac{90}{2}=\boxed{\bf45}\\\\\text{the sums of the numbers in each row, in each column are }=\frac{45}{3}=\boxed{\bf15}\\\\\text{Solution:}\\\\\boxed{\,2\,}\boxed{\,7\,}\boxed{\,6\,}\\\boxed{\,9\,}\boxed{\,5\,}\boxed{\,1\,}\\ \boxed{\,4\,}\boxed{\,3\,}\boxed{\,8\,}\\\\\text{Convenient rotation of the square gives 8 solutions.}[/tex]
The overhead reach distances of adult females are normally distributed with a mean of 205 cm205 cm and a standard deviation of 8.6 cm8.6 cm.
a. Find the probability that an individual distance is greater than 215.00215.00 cm.
b. Find the probability that the mean for 2525 randomly selected distances is greater than 203.70 cm.203.70 cm.
c. Why can the normal distribution be used in part (b), even though the sample size does not exceed 30?
Answer:
a) P(z>1.16) = 0.8770
b) P(z>-0.75) = 0.2266
Step-by-step explanation:
Mean = 205 cm
Standard Deviation = 8.6 cm
a) Find the probability that an individual distance is greater than 215.00
We need to find P(X>215)
x = 215
z = x - mean /standard deviation
z = 215 - 205 / 8.6
z = 1.16
P(X>215)=P(z>1.16)
Finding value of z =1.16 from the table
P(z>1.16) = 0.8770
b) Find the probability that the mean for 25 randomly selected distances is greater than 203.70 cm
Sample size n= 25
x = 203.70
mean = x- mean / standard deviation / √sample size
mean = 203.70 - 205 / 8.6 / √25
mean = -1.3/8.6/5
mean = -0.75
Finding value from z-score table
P(mean >-0.75) = 0.2266
c) Why can the normal distribution be used in part (b), even though the sample size does not exceed 30?
If the original problem is normally distributed, then for any sample size n, the sample means are normally distributed.
Martin runs 100 meters in 15 seconds. What is the equation for d, the distance in meters that Martin covers per second
Answer:
d = 6.67s
Step-by-step explanation:
This is the answer because if you take 100 and divide it by 15, then you get d as 6.6666, which rounds up to 6.67s.
Among two supplementary angles the measure of the larger angle is 44 more than
the measure of the smaller. Find their measures.
Please reply soon
The one who replies first I will answer all their questions ...............
Answer:
The smaller angle= 68°
The larger angle=112°
Step-by-step explanation:
Supplementary angles add up to 180°
Let the smaller of the angles to x then the larger angle will be x+44.
Adding the two then equating to 180°:
x+(x+44)=180
2x+44=180
2x=180-44
2x=136
x=68
The smaller angle= 68°
The larger angle=68+44=112°
Answer:
The angles are 68° , 112°
Step-by-step explanation:
Let the smaller angle be x
so the larger angle = x + 44
x , x + 44 are supplementary.
so, x + (x + 44) = 180
x + x + 44 = 180
2x = 180 - 44 = 136
x = 136/2 = 68
the larger angle = x + 44 = 68 + 44 = 112
If f(x)= -3x-2 ,what is f(-5)
Answer:
f(- 5) = 13
Step-by-step explanation:
To evaluate f(- 5) substitute x = - 5 into f(x)
f(- 5) = - 3 × - 5 - 2 = 15 - 2 = 13
This circle is centered at the origin, and the length of its radius is 6. What is
the circle's equation?
Answer:
x² + y² = 36
Step-by-step explanation:
The equation of a circle centred at the origin is
x² + y² = r² ← r is the radius
here r = 6, so
x² + y² = 6², that is
x² + y² = 36
The circle's equation is x² + y² = 36.
What is the equation for a circle?The equation of a circle provides an algebraic way to describe a circle, given the center and the length of the radius of a circle.The equation of a circle is different from the formulas that are used to calculate the area or the circumference of a circle.Given:
length of its radius is 6.
To find:
the circle's equation
The equation for a circle in center, radius form is
(x - h)² + (y - k)² = r²
The equation of a circle centered at the origin is
x² + y² = r²
Where, r is the radius of the circle
Here radius of the circle = 6
If the center is (0,0) then h = 0 and k = 0
x² + y² = 6²,
x² + y² = 36
Therefore, the circle's equation x² + y² = 36.
To learn more about the radius of the circle refer to:
https://brainly.com/question/12051783
#SPJ2
What is the equation of the line that goes through the point (6,-1) and is parallel to the line represented by the equation below?
y=-5/6 x+3
A. y= -5/6x + 4
B. y= -5/6x - 6
C. y= -5/6x -4
D. y= -5/6x + 6
[tex]\huge{\boxed{y=-\frac{5}{6} x+4}}[/tex]
Parallel lines share the same slope, so the slope of the parallel line in this case must be [tex]-\frac{5}{6}[/tex].
Point-slope form is [tex]y-y_1=m(x-x_1)[/tex], where [tex]m[/tex] is the slope and [tex](x_1, y_1)[/tex] is any known point on the line.
Plug in the values. [tex]y-(-1)=-\frac{5}{6} (x-6)[/tex]
Simplify and distribute. [tex]y+1=-\frac{5}{6} x+5[/tex]
Subtract 1 from both sides. [tex]\boxed{y=-\frac{5}{6} x+4}[/tex]
Answer:
y = -5/6x + 4 (slope - intercept form)
OR
5x + 6y -24 = 0 (standard form)
Step-by-step explanation:
What is the equation of the line that goes through the point (6,-1) and is parallel to the line represented by the equation below?
y=-5/6 x+3
To solve this;
We need to first find the slope of the the equation given
Comparing the equation given with y=mx + c, the slope (m) = -5/6, any equation parallel to this equation will have the same slope as this equation.
Since our new equation is said to be parallel to this equation the slope(m) of our new equation is also -5/6.
Now we will proceed to find the intercept of our new equation, to find the intercept, we will simply plug in the value of the points given and the slope into the formula y=mx + c and then simplify
The value of the points given are; (6, -1) which implies x=6 and y=-1 slope(m)= -5/6
y = mx + c
-1 = -5/6 (6) + c
-1 = -5 + c
Add 5 to both-side of the equation to get the value of c
-1+5 = -5+5 + c
4 = c
c=4
Therefore the intercept(c) of our new equation is 4
We can now proceed to form our new equation. To form the equation, all we need to do is to simply insert the value of our slope (m) and intercept (c) into y = mx + c
y = -5/6x + 4
This above equation is in slope-intercept form, we can further simplify it to be in the standard form.
6y = -5x + 24
5x + 6y -24 = 0
Given the following coordinates complete the reflection transformation. A(1,−5) B(2,−2) C(5,−2) Transformation: Complete the double reflection over the lines y=−1 followed by y=1. A"( , ) B"( , ) C"( , )
Answer:
A''(1,-1) B''(2,2) C''(5,2)
Step-by-step explanation:
Points A(1,−5) B(2,−2) C(5,−2)
reflection over y=-1
Perpendicular distance between points y-coordinates of points (A, B and C) and y=-1 are 4,1 and 1
after reflections, the perpendicular distance will be 8,2,2 and the points will be at
A'(1,3) B'(2,0) C'(5,0)
again reflection over y=1
Perpendicular distance between points y-coordinates of points (A', B' and C') and y=1 are 2,1 and 1
after reflections, the perpendicular distance will be 4,2,2 and the points will be at
A''(1,-1) B''(2,2) C''(5,2)!
what is the length of chord ab
Answer:
AB=20
Step-by-step explanation:
Given:
r= 14.5
AB cuts r=14.5 in two parts one parts length=4
remaining length, x = 14.5 - 4 =10.5
draw a line from center of circle to point A making right angled triangle
Now hypotenuse=r=14.5
and one side of triangle=10.5
Using pythagoras theorem to find the third side:
c^2=a^2+b^2
14.5^2=10.5^2+b^2
14.5^2-10.5^2=b^2
b^2=100
b=10
AB=2b
=2(10)
=20
Hence length of cord AB=20!
What is the value of x?
A. 155°
B. 60°
C. 35
D. 25°
Answer: C
Step-by-step explanation:
First, you should see that the bottom right corner is an angle on the other side. So subtract 180 from 95 to get 85. Since all angles in a triangle add up to 180, You do 85 + 60 + x = 180. You simplify further to get 145 + x = 180.
Subtracting 145 from both sides leaves you with x = 35, which gives you C.
So C is the correct answer.
the sum of two consecutive numbers is 1107. what are those numbers
PLEASE HELP !!!!!!!
[tex]\huge{\boxed{553}}\ \ \huge{\boxed{554}}[/tex]
The numbers can be represented as [tex]x[/tex] and [tex]x+1[/tex].
We know that [tex]x+x+1=1107[/tex].
Combine like terms. [tex]2x+1=1107[/tex]
Subtract 1 on both sides. [tex]2x=1106[/tex]
Divide both sides by 2. [tex]x=553[/tex]
The first number is [tex]x[/tex], which equals [tex]\boxed{553}[/tex].
The second number is [tex]x+1[/tex], which equals [tex]553+1[/tex], which is [tex]\boxed{554}[/tex].
These numbers can be presented as n and n + 1 = 1107
2n = 1106 because we combine the n terms and subtract 1 from each side.
2n ÷ 2 = n
1106 ÷ 2 = 553
We now know that n = 553.
Our second consecutive integer must be 554. This is because our second
consecutive integer represents n + 1 so 553 + 1 =554.
Therefore, are two consecutive integers are 553 and 554.
What else would need to be congruent to show that ABC = XYZ by ASA?
Answer:
Option B AC≅XZ
Step-by-step explanation:
we know that
ASA (angle, side, angle) means that we have two congruent triangles where we know two angles and the included side are equal
In this problem we have
∠X≅∠A
∠Z≅∠C
In the triangle ABC the included side between the angles ∠A and ∠C is the side AC
and
In the triangle XYZ the included side between the angles ∠X and ∠Z is the side XZ
therefore
AC≅XZ
using the discriminant, how many solutions and what type of solution(s) does k^2-10k+25=0 have?
a. 2; irrational
b. 2; rational
c. 1; rational
d. no real solutions
Answer:
c. 1; rational
Step-by-step explanation:
k² − 10k + 25 = 0
The discriminant of ax² + bx + c is b² − 4ac.
If the discriminant is negative, there are no real roots.
If the discriminant is zero, there is 1 real root.
If the discriminant is positive, there are 2 real roots.
If the discriminant is a perfect square, the root(s) are rational.
If the discriminant isn't a perfect square, the root(s) are irrational.
Finding the discriminant:
a = 1, b = -10, c = 25
(-10)² − 4(1)(25) = 0
The discriminant is zero, so there is 1 rational root.
What is the sum of sqrt -2 and sqrt -18
Answer:
4i sqrt(2)
Step-by-step explanation:
sqrt(-2) + sqrt(-18)
We know sqrt(ab)= sqrt(a) sqrt(b)
sqrt(-1)sqrt(2) + sqrt(9) sqrt(-2)
sqrt(-1)sqrt(2) + sqrt(9) sqrt(2)sqrt(1)
We know the sqrt(-1) is equal to i
i sqrt(2) +3 sqrt(2) i
i sqrt(2) +3i sqrt(2)
4i sqrt(2)
A particular model of walkie-talkie can broadcast in a circular area. The radius of the broadcast area is 7,000 feet. Find the area of this circle to the nearest square foot. Use 3.14 for π.
Answer:
153938040.0259 ft2
Step-by-step explanation:
R= Square root of A/π
Answer:
153,860,000 ft^2.
Step-by-step explanation:
The area = 3.14 * r^2
= π * 7,000^2
= 153,860,000 ft^2.
Max is drawing plans for a garden, measured in feet, which is shown below on the coordinate plane. Max has two vertices
of the garden at points (-1, 2) and (-1,-2).
At which points should Max have the other two vertices in order to make the area of his garden 20 square feet?
Answer:
The other two vertices are (4 , -2) and (4 , 2) ⇒ 2nd answer
Step-by-step explanation:
* Lets explain how to solve the problem
- All the points on a vertical line have thee same x-coordinates
- In the vertical segment whose endpoints are (x , y1) and (x , y2)
its length = y2 - y1
- All the points on a horizontal line have thee same y-coordinates
- In the horizontal segment whose endpoints are (x1 , y) and (x2 , y)
its length = x2 - x1
* Lets solve the problem
- The two vertices of the garden are (-1 , 2) , (-1 , -2)
- The side joining the two vertices is vertical because the points have
the same x-coordinate
∴ The length of the height = 2 - -2 = 2 + 2 = 4
∴ The length of the height of the garden is 4 feet
∵ The garden shaped a rectangle
∵ The area of the garden is 20 feet²
- The area of the rectangle = base × height
∵ The height = 4 feet
∴ 20 = base × 4 ⇒ divide both sides by 4
∴ Base = 5 feet
∴ The length of the base of the garden is 5 feet
- The adjacent side to the height of the rectangle is horizontal line
∵ The points on the horizontal line have the same y-coordinates
∴ The adjacent vertex to vertex (-1 , 2) has the same y-coordinates 2
∵ The length of the horizontal segment is x2 - x1
∴ 5 = x - (-1)
∴ 5 = x + 1 ⇒ subtract 1 from both sides
∴ x = 4
∴ The adjacent vertex to (-1 , 2) is (4 , 2)
- Lets find the other vertex by the same way
∵ The adjacent vertex to vertex (-1 , -2) has the same y-coordinates -2
∵ x-coordinate of this vertex is the same with x- coordinate of point
(4 , 2) because these two points formed vertical side
∴ The other vertex is (4 , -2)
∴ The adjacent vertex to (-1 , -2) is (4 , -2)
* The other two vertices are (4 , -2) and (4 , 2)
Answer: Option B
(B) (4,-2) and (4,2) <======+ 100%
Step-by-step explanation:
I need help on number 2 please, would really appreciate the help!
Answer:
1st piece = 15 inch
2nd piece = 15 inch
3rd piece = 30 inch
Step-by-step explanation:
2.
Let length of first piece be x
since 2nd piece is same, so 2nd piece's length is also x
third piece is TWICE, so its length is 2x
Total length of all the 3 pieces is 60, so we setup an equation and solve for x:
x + x + 2x = 60
4x = 60
x = 60/4 = 15
Hence, first piece is 15, second piece is 15, third piece is 2(15) = 30
simplify the following fraction (5/9x3/5)+6/7
Answer:
1 4/21
Step-by-step explanation:
(5/9*3/5)+6/7
The 5's cancel
(3/9)+6/7
Cancel a 3 in the numerator and a 3 in the denominator
1/3 + 6/7
We need to get a common denominator of 21
1/3 *7/7 + 6/7 *3/3
7/21 + 18/21
25/21
This is an improper fraction
21 goes into 25 1 time with 4 left over
1 4/21
Answer: [tex]\frac{25}{21}[/tex]
Step-by-step explanation:
The first step is to make the multiplication of the fractions inside the parentheses. To do this, you must multiply the numerator of the first fraction by de numerator of the second fraction and the denominator of the first fraction by the denominator of the second fraction:
[tex](\frac{5}{9}*\frac{3}{5})+\frac{6}{7}=\frac{15}{45}+\frac{6}{7}[/tex]
Now you can reduce the fraction [tex]\frac{15}{45}[/tex]:
[tex]=\frac{1}{3}+\frac{6}{7}[/tex]
And make the corresponding addition: in this case the Least Common Denominator (LCD) will be the multiplication of the denominators. Divide each denominator by the LCD and multiply this quotient by the corresponding numerator and then add the products. Therefore you get:
[tex]=\frac{7+18}{21}=\frac{25}{21}[/tex]
What mistake did the student make?
Answer:
A
Step-by-step explanation:
if he had multiplied the 2nd equation by 9 throughout successfully, he would have gotten :
6x - y = 16 (multiply by 9)
54x - 9y = 144
Answer:
(a) The error is in step 1.
See below.
Step-by-step explanation:
They did not multiply the 16 by 9.
Which of the following expressions is this one equivalent to?
[tex]( {x}^{4}+ 2 {x}^{3} - x - 2) \div ( {x}^{3} - 1) [/tex]
___________________________________________
○A.
[tex] {x}^{2} + x + 1[/tex]
○B.
[tex] {x}^{2} + 3x + 2[/tex]
○C.
[tex]x + 2[/tex]
○D.
[tex]2x - 5 - \frac{3}{ {x}^{3} - 1 } [/tex]
Answer:
○C. x + 2
Step-by-step explanation:
x^4 + 2x^3 -x-2
-------------------------
x^3 -1
Factor the numerator by grouping. Take an x^3 from the first 2 terms and -1 from the last 2 terms
x^3( x + 2) -1(x+2)
-------------------------
x^3 -1
now lets factor out the x+2
( x + 2)(x^3 -1)
-------------------------
x^3 -1
Canceling out the x^3-1, we are left with
x+2
Answer:
C. x+2
Step-by-step explanation:
The given expressions are two polynomials which have to be divided in order to find the quotient. The long division method will be used to find the quotient of the two terms.
The long division is done and the picture is attached for detail.
From the picture, we can see that the correct answer is:
C. x+2 ..
Jill has quiz scores of 74, 72, 76, 80, and 73. To continue to receive her scholarship, Jill must maintain an average of 75. What is the lowest grade Jill needs to have on the next quiz to keep her scholarship?
A. 77
B. 75
C. 73
D. 71
Answer:
B
Step-by-step explanation:
(74+72+76+80+73+(AnswerB)75)÷6(total number of quizzes include the one she needed to take)=75(minimum average because she needs to get average of 75)
Evaluate the function rule for the given value. f(x) = 3^x for x = –5
Answer:
f(-5) = 1/ 243
Step-by-step explanation:
f(x) = 3^x
Let x=-5
f(-5) = 3^-5
Since the exponent is negative, it will move to the denominator
f(-5) = 1/3^5
f(-5) = 1/ 243
For this case we have the following function:
[tex]f (x) = 3 ^ x[/tex]
We must evaluate the function for[tex]x = -5[/tex]
So, we have:
[tex]f (-5) = 3 ^ {-5}[/tex]
By definition of power properties it is fulfilled that:
[tex]a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}[/tex]
Thus:
[tex]f (-5) = \frac {1} {3 ^ 5} = \frac {1} {3 * 3 * 3 * 3 * 3} = \frac {1} {243}[/tex]
Answer:
[tex]\frac {1} {243}[/tex]
Which of the following disjunctions is false?
2 · 3 = 6 or 4 + 5 = 10
5 - 3 = 2 or 3 · 4 = 12
3 + 4 = 9 or 5 · 2 = 11
6 · 2 = 11 or 3 + 5 = 8
Answer:
Option C 3 + 4 = 9 or 5 · 2 = 11 is correct answer
Step-by-step explanation:
Disjunction states that if we have p or q then the disjunction is true if either p is true or q is true or p and q are true.
The disjunction is false when both p and q both are false.
1. 2 · 3 = 6 or 4 + 5 = 10
Disjunction is true because 2.3 =6 is true while 4+5=10 is false
2. 5 - 3 = 2 or 3 · 4 = 12
Disjunction is true because 5-3 =2 is true and 3.4=12 is also true.
3. 3 + 4 = 9 or 5 · 2 = 11
Disjunction is false because 3+4 =7 and not 9 and 5.2 =10 and not 11. Since both are false so, this disjunction is false.
4. 6 · 2 = 11 or 3 + 5 = 8
Disjunction is true because 6.2=12 and not 11 is false but 3+5 = 8 is true.
So, Option C 3 + 4 = 9 or 5 · 2 = 11 is correct answer.
What is the explicit rule for the geometric sequence?
9.5,1.9,0.38,0.076,...
Answer:
[tex]a_n=9.5 \cdot (0.2)^{n-1}[/tex]
Step-by-step explanation:
If this is a geometric sequence, it will have a common ratio.
The common ratio can be found by dividing term by previous term.
The explicit form for a geometric sequence is [tex]a_n=a_1 \cdot r^{n-1} \text{ where } a_1 \text{ is the first term and } r \text{ is the common ratio}[/tex]
We are have the first term is [tex]a_1=9.5[/tex].
Now let's see this is indeed a geometric sequence.
Is 0.076/0.38=0.38/1.9=1.9/9.5?
Typing each fraction into calculator and see if you get the same number.
Each fraction equal 0.2 so the common ratio is 0.2.
So the explicit form for our sequence is
[tex]a_n=9.5 \cdot (0.2)^{n-1}[/tex]
Final answer:
A geometric sequence follows a specific pattern where each term is obtained by multiplying the previous term by a constant ratio. The explicit rule for a geometric sequence is defined by the first term, the term number, and the common ratio.
Explanation:
Geometric series are sequences in which each term after the first is found by multiplying the previous term by a fixed, non-zero number called the common ratio. The explicit rule for a geometric sequence is of the form an = a₁ * r⁽ⁿ⁻¹⁾, where a₁ is the first term, n is the term number, and r is the common ratio.
SOLVE 4x + 3y = –5 -2x + 2y = 6 BY USING ELIMINATION. SHOW ALL WORK!!! HELPPPP :)))) THANKS! ;)
Answer:
x= [tex]\frac{-1}{6}y+\frac{-11}{6}[/tex]
y=6x+11
Step-by-step explanation:
4x + 3y = –5 -2x + 2y = 6
- 4x - 3y –5 -2x + 2y = 6
- 4x - 3y -2x + 2y = 6+5
-4x - 3y -2x +2y =11
-6x-y= 11
Solve the system using substitution. y=-2x+12 3y-x+6=0. What is the solution?
Answer:
x = 6, y = 0 → (6, 0)Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}y=-2x+12&(1)\\3y-x+6=0&(2)\end{array}\right\qquad\text{substitute (1) to (2):}\\\\3(-2x+12)-x+6=0\qquad\text{use the distributive property}\\(3)(-2x)+(3)(12)-x+6=0\\-6x+36-x+6=0\qquad\text{combine like terms}\\(-6x-x)+(36+6)=0\\-7x+42=0\qquad\text{subtract 42 from both sides}\\-7x=-42\qquad\text{divide both sides by (-7)}\\\boxed{x=6}\qquad\text{put it to (1)}\\\\y=-2(6)+12\\y=-12+12\\\boxed{y=0}[/tex]
Answer:
[tex]\text{\fbox{(6,~0)}}[/tex]
Step-by-step explanation:
[tex]\left \{ {{\text{y~=~-2x~+~12}} \atop {\text{3y~-~x~+~6~=~0}} \right. \\ \\ \text{We~already~have~the ~value~of ~y ~so~ substitute~ this~ value~~ of ~y ~into~ the ~second ~equation.} \\ \\ \text{3(-2x~+~12)~-~x~+~6~=~0} \\ \\ \text{Distribute~ 3 ~inside~ the~ parentheses.} \\ \\ \text{-6x~+~36~-~x~+~6~=~0} \\ \\ \text{Combine~ like~ terms. ~You ~can~ subtract~ -6x ~and ~x ~and ~add ~36 ~and ~6.} \\ \\ \text{-7x~+~42~=~0} \\ \\ \text{Subtract~ 42 ~from~ both~ sides ~of~ the ~equation.} \\ \\ \text{-7x~=~-42} \\ \\ \text{Now ~solve~ for ~x ~by ~dividing~ both~ sides ~by~ -7.} \\ \\ \text{\fbox{x~=~6}} \\ \\ \text{To~ find~ y, ~substitute~ 6 ~for~x~ into~ the~first~ equation.} \\ \\ \text{y~=~-2(6)~+~12} \\ \\ \text{Multiply ~-2~ and~ 6.} \\ \\ \text{y~=~-12~+~12} \\ \\ \text{Combine~ like ~terms~ to ~complete~ solving~ for ~y.} \\ \\ \text{\fbox {y~=~0}} \\ \\ \text{The~ solution~ to ~this ~system ~of ~equations ~is ~\fbox{(6~,~ 0)}~.}[/tex]
[tex]\text{x~=~6} \\ \text{y~=~0}[/tex]Perform the indicated operation.
3k+6/(k-2)+(2-k)= answers::: 3, -3,3k+6/k-2,3k+6/k+2
Answer:
3 is the correct option.
Step-by-step explanation:
The given expression is:
3k+6/(k-2)+(2-k)
Break the numerators:
3k/(k-2) + 6/(2-k)
Now Re-arrange the term (2-k) in the denominator as (-k+2)
3k/(k-2) + 6/(-k+2)
Now takeout -1 as a common factor from (-k+2)
3k/(k-2) + 6/-1(k-2)
Now move a negative (-1)from the denominator of 6/-1(k-2) to the numerator
3k/(k-2) + -1*6/(k-2)
Now take the L.C.M of the denominator which is k-2 and solve the numerator
3k - 6/ (k-2)
Take 3 as a common factor from the numerator:
3(k-2)/(k-2)
k-2 will be cancelled out by each other:
Thus the answer will be 3.
The correct option is 3....
What is the reference angle for 120°
Check the picture below.
bearing in mind that in essence, a reference angle is the angle made with the x-axis from any terminal point.
For triangle ABC, which one is equivalent to sin(A)?
cos(B)
sin(B)
cos(C)
tan(C)
Answer: cos(C)
Step-by-step explanation: Use SohCahToa. Sin(A) is opposite over hypotenuse. The opposite is line BC. Use angle C. To get line BC, you will need the adjacent, and also the hypotenuse. Cos will get you this. Therefore, your answer is Cos(C).
The one which is equivalent to [tex]sin(A)[/tex] will be [tex]Cos(C)[/tex] .
What are trigonometric ratios ?Trigonometric ratios are real functions which relate an angle of a right-angled triangle to ratios of two side lengths.
There are six trigonometric ratios [tex]Sin\theta,Cos\theta,Tan\theta,Cot\theta,Sec\theta,Cosec\theta[/tex] .
We have,
[tex]\triangle ABC[/tex] Right angled at [tex]B[/tex] .
So,
[tex]sin(A)=\frac{Perpendicular}{Height}[/tex]
So, in [tex]\triangle ABC[/tex] ,
[tex]sin(A)=\frac{BC}{AC}[/tex]
Now,
To find its equivalent we will look from angle [tex]C[/tex] ,
So, in options we two trigonometric ratios from angle [tex]C[/tex],
So, take [tex]Cos(C)[/tex] ,
[tex]Cos(C)=\frac{Base}{Hypotenuse}[/tex]
[tex]Cos(C)=\frac{BC}{AC}[/tex]
i.e. Equivalent to [tex]sin(A)[/tex] is [tex]Cos(C)[/tex]
Hence, we can say that the one which is equivalent to [tex]sin(A)[/tex] will be [tex]Cos(C)[/tex] which is in option [tex](c)[/tex] .
To know more about trigonometric ratios click here
https://brainly.com/question/1201366
#SPJ3